REPRESENTASI KECANTIKAN DALAM IKLAN: (Analisis Semiotika Roland Barthes pada Iklan 25 Tahun Wardah di Youtube) - Savira Amanda, (2021)
The concept of true beauty is a relative thing. However, without realizing it, beauty has a standardization that is constructed through impressions in the media, one of which is advertising. Advertising is a means to promote a product to the general public, including beauty products. The purpose of this study was to determine the representation of beauty in the advertisement "25 Years of Wardah - Cantikmu Siap Hadapi Dunia" using the semiotic study of Roland Barhtes. This study uses a qualitative approach. Data collection techniques were carried out through observation on the advertising analysis unit "25 Tahun Wardah - Cantikmu Ready to Face the World" and also through library sources. The results showed that the representation of women's beauty in the advertisement "25 Tahun Wardah - Cantikmu Ready to Face the World" was not only shown through an attractive appearance but also a positive attitude contained in women.